Means of Lexical Representation of Spatial Continuum in Early Stories of I. A. Bunin - M. A. Dubova (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The question of ways of creating a spatial continuum in the early stories of I. A. Bunin “On the wrong side”, “On the farm” and “On the Donets”, united by a single principle of nomination and included in the first book of the writer’s prose “To the end of the world” (1897) is considered in the article. The semantics of the title actualizes the spatial component of the author’s linguistic picture of the world, which determined the path of linguistic and stylistic analysis of the linguistic material of stories. The authors pay special attention to the means of lexical representation of space as one of the basic linguo-cognitive categories. The novelty of the research lies in the fact that the language material has been identified, systematized and described, which makes it possible to determine the individual author's characteristics in the creation of the spatial continuum of I. A. Bunin’s early stories. The relevance of the study is due to the appeal to the problems of cognitive linguistics. On the basis of statistical, descriptive and linguo-cognitive methods of analysis, the authors identify and describe the means of lexical representation of the spatial model created in the stories of I. A. Bunin, which is characterized by a clear structuredness and individuality of the author’s approach. In the course of the study, the authors come to conclusions that make it possible to characterize the features of the construction of space in the early stories of the writer, taking into account the individual characteristics of the author's world modeling, and also to analyze the linguistic parameters of the idiostyle of I. A. Bunin.